The use of an optimisation model to design a green supply chain: A case study of the Thai rubber industry. Issue 2 (8th August 2016) - Chanchaichujit, Janya; Saavedra-Rosas, Jose; Quaddus, Mohammed; West, Martin
Abstract : Purpose: This paper aims to take the first step in solving environmental supply chain management issues. It proposes a green supply chain management (GSCM) model which would provide environmental benefits to the Thai rubber industry. To this end, a GSCM optimisation model was formulated, whereby the manufacturing processes of rubber products, along with their distribution and transportation, could be improved. The expected result is that total greenhouse gas emissions would be minimised and environmental performance maximised. Design/methodology/approach: Linear programming was chosen as the mathematical programming for investigation into the problem of finding the association of quantity of rubber product flow between the supply chain entities ( farmer, trader group, and factory ) and the transportation mode and route, with a view to minimise total greenhouse gas emissions. Findings: The results indicate that by using the proposed model, GHG emissions could be minimised to 1.08 tons of GHGs per ton of product. Practical implications: A Green Supply Chain Management Model developed in this research can be used as a decision support tool for Thai Rubber policy makers. This would allow them to better manage the Thai Rubber industry to achieve environmental benefit. Originality/value: This research is among the first attempts to develop a Green Supply Chain Management (GSCM) model for the Thai Rubber industry. It can contribute to providing a basis for a GSCM modelling framework, along with a formulation for research development in this area.